Acid‐Catalyzed Synthesis of α, β‐Disubstituted Conjugated Enones by a Meyer–Schuster‐Type Rearrangement in Allenols. Issue 5 (12th March 2015) - Alcaide, Benito; Almendros, Pedro; Cembellín, Sara; Martínez del Campo, Teresa
Abstract A novel, direct and simple methodology to gain access to α, β‐disubstituted conjugated enones from α‐allenols in a sustainable metal catalysis context, considering the inexpensiveness and environmentally friendliness of iron(III) species and protons, has been developed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>